Theoretical Foundations of the Process of Steaming Cocoons in a Vacuum Device - Kodirov Ziyodulla Abdumuxtarovich; Parpiyev Sayfidin Fazliddinovich (Research Parks Publishing LLC, 2022)
This article highlights the importance of the cocoon steaming process for producing quality raw silk. And also provides information about the advantage of vacuum cocoon steamer. Since the vacuum pressure, temperature and volume of water in the evaporation chamber are constant, isobaric, isothermal and isochoric processes of thermodynamics are also studied. Information on absorption and adsorption processes associated with the entry of liquid into the cocoon is also provided.